A redescription of Rheotanytarsus lamellatus Reiss in all stages (Diptera: Chironomidae) and new records from Argentina - Tejerina, Eva Gabriela (2009)
Immature stages and adult female of Rheotanytarsus lamellatus Reiss are described for the first time, and the male is redescribed, diagnosed and compared with R. meridionalis (Johannsen). Both species are reported for the first time from Argentina. Keys to South American male adults and pupae are given.